The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2318-08892016000200004
|View full text |Cite
|
Sign up to set email alerts
|

Use of social network to support visually impaired people: A Facebook case study

Abstract: The use of Information and Communication Technologies can be seen as an important factor for social inclusion in its different aspects -economic, social, relational and informational, among others. Inclusion potentiality is even more relevant for groups of people who face limiting life conditions which determine social barriers. This study investigated the social support offered to people with disabilities based on the social network analysis method. The research objective was to make the online support dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Therefore, librarians should be trained on how to relate to PWDs. For example, studies have shown that visually impaired people use a more interpersonal medium when seeking information (Caran et al, 2016; Wang and Yu, 2017). It is therefore important that librarians be given periodic training on how best to serve this category of users.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, librarians should be trained on how to relate to PWDs. For example, studies have shown that visually impaired people use a more interpersonal medium when seeking information (Caran et al, 2016; Wang and Yu, 2017). It is therefore important that librarians be given periodic training on how best to serve this category of users.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, there were many social network research use NodeXL to explore the relationship between users [7][8][9][10][11][12][13]. Nevertheless, this is the first study exploring how government officials use the Facebook fan page to promote policies and analyze the interaction between agencies and people by using a social network analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When they do participate, they share common experiences, societal concerns, and information about disability issues as well as policies that concern them (Stetten et al, 2019). In a case study, the majority of members in a Facebook group for people with visual impairment were found not to actively participate in it by posting (Caran et al, 2016). However, it was suggested that members may have been expressing their emotional support to each other by liking posts (Caran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%